1989
DOI: 10.1093/aepp/11.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Managerial Performance and Income Variability for a Sample of Illinois Cash Grain Producers

Abstract: Managerial ability generally is considered a key determinant of success in farming. This analysis evaluates managerial performance over the period 1976–1983 for a sample of 179 Illinois cash grain producers. Characteristics of the superior and inferior performing groups are presented and the variability of performance is assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…Since Patrick and Eisgruber (1968) showed that managerial skill leads to firm growth and superior performance, researchers have attempted to shed more light on exactly how managerial skill influences firm performance (Sonka et al 1989;Nuthall 2006;Nuthall 2009). Managerial skill is a function of the characteristics of the manager, including experience and education (Nuthall 2009), along with the knowledge of market dynamics facing the manager (Day 1994;Barney et al 2001).…”
Section: Previous Literaturementioning
confidence: 99%
“…Since Patrick and Eisgruber (1968) showed that managerial skill leads to firm growth and superior performance, researchers have attempted to shed more light on exactly how managerial skill influences firm performance (Sonka et al 1989;Nuthall 2006;Nuthall 2009). Managerial skill is a function of the characteristics of the manager, including experience and education (Nuthall 2009), along with the knowledge of market dynamics facing the manager (Day 1994;Barney et al 2001).…”
Section: Previous Literaturementioning
confidence: 99%
“…The magnitude of this statistic is reasonably high because of the cross-sectional nature of the data. According to Sonka, Hornbaker, and Hudson (1989), obtaining the McFadden pseudo-R 2 in the range of 0.2 to 0.4 is typical in the case of qualitative choice models. The pseudo-R 2 , proposed by McKelvey and Zavoina (1975), which is considered to be the best measure to use for binary choice models [Windmeijer (1995)], is calculated to be 0.39.…”
mentioning
confidence: 99%
“… McFadden's R 2 is calculated as: where log L 0 is the value of log‐likelihood function subject to the constraint that all regression coefficients except the constant term are zero, and log L ( β ) is the maximum value of the log‐likelihood function without constraints (Veall and Zimmerman, 1996). McFadden R 2 in the range of 0.2–0.4 are typical for logit models (Sonka et al. , 1989).…”
mentioning
confidence: 99%